(untitled) (Research, Society and Development, 2022)
The use of medicinal plants does not depend on the prescription of health professionals, however, some of them can be hepatotoxic and/or nephrotoxic, interact with other drugs, as well as affect the results of laboratory tests. This study aimed to review the literature on medicinal plants that interfere with laboratory test results. This review is a narrative study, with no time frame. The search was carried out on the websites of virtual libraries, platforms and national and international databases: Biblioteca Virtual da Saúde (BVS), Periódicos Capes, Scielo, US National Library of Medicine (PubMed) and Google Scholar, in addition to national journals that publish on medicinal plants, clinical analysis, clinical pathology or medical laboratory. Medicinal plants alter the results of laboratory tests by three mechanisms: 1) direct interference in the test, 2) physiological effects, and 3) the effect of contaminants. Interferences in vitro (chemical) or in vivo (physiological) do not always have defined mechanisms. Peumus boldus (boldo), Mikania glomerata (guaco) and Matricaria chamomilla (chamomile) interfere by physiological mechanisms and the plants Aspidosperma macrocarpum (guatambu do cerrado), Solanum melongena L. (eggplant), Melissa officinalis (lemon balm), Cymbopogon citratus (lemon grass), Peumus boldus (boldo) and Melissa officinalis (true lemon balm) interfere in vitro, directly interfering with the tests. It is concluded that is necessary to collect as much information as possible during the client/patient registration in the laboratory, to be aware of what interferes with the tests, and habits of patients that may be related to unexpected test results.